Agronomic and marketing characteristics of peanut genotypes in the Northeast Mesoregion of Mato Grosso - Agulhon, Fabiano de Souza (2022)
This study aimed to evaluate the agronomic and marketing characteristics of peanut genotypes in the northeastern mesoregion of the state of Mato Grosso. The experiment was carried out in the agricultural year 2021/22, at Fazenda Santo Antônio, located in the municipality of Santo Antônio do Leste-MT. The experimental design was in randomized blocks, with four replications. The treatments were ten runner peanut genotypes, one cultivar (BRS 421 OL) and nine lines (2259 OL, 3003 OL, 2091 OL, 2946 OL, 2960 OL, 2988 OL, 2991 OL, 1253 OL and 2055 OL), developed by EMBRAPA's PMA. The plots consisted of two lines of three meters in length, spacing of 0.90 m, interval between plots of two meters and plot area of ​​5.4 m2. The harvest was carried out at 140 days after planting. The parameters evaluated were black spot severity (Nothopassalora personata), broken grains (%), yield (%), granulometry (mass of 100 grains and sieves) and pod productivity. There was variability of granulometry in the different sieves, being able to be directed to different market niches. The lowest severities were obtained with the 3003 OL, BRS 421 OL and 2091 OL. The highest yields were obtained in the genotypes 2259 OL, 3003 OL, BRS 421 OL, 1253 OL, 2946 OL and 2988 OL, under these soil and climate conditions in the Northeast mesoregion of the state of Mato Grosso.